Equality & revolution : women's rights in the Russian Empire, 1905-1917 - Ruthchild, Rochelle Goldberg (Series in Russian and East European studies., 2010)
""Ruthchild argues that the women's movement in Russia, with its insistence on women's citizenship and suffrage, was integral to democratization efforts in Imperial Russia, and especially to the revolutions of 1917. Her book is deeply researched, carefully crafted, and beautifully written. By providing a gendered interpretation of Russian political history, by insisting on individual agency and biography, she has provided an astute work of historiography as well as a masterpiece of historical reconstruction."--Karen Offen, Stanford University" ""Equality and Revolution chronicles the fascinating story of the rise of feminism and suffrage in late tsarist Russia, showing us a society in upheaval over its core identity. Ruthchild has given us a page-turning account that brings an era and a movement to life, demonstrating how far the notion of democracy could go in a revolutionary epoch."--Elizabeth Wood, Massachusetts Institute of Technology" "On July 20, 1917, Russia became the first major power to grant women the right to vote and hold public office. But after the October Revolution and the establishment of the Soviet Union, those who had pioneered the suffragist cause were all but erased from accounts of Russian history. The women's movement, when mentioned at all, was portrayed as rooted in the elitist and bourgeois culture of the tsarist era, meaningless to proletarian and peasant women, and even counter to socialist ideology. In this highly original and historically revisionist study, Rochelle Goldberg Ruthchild reveals that in fact Russian feminists appealed to all classes and were an integral force for revolution and social change. She profiles the individuals and organizations that were vital to the feminist struggle, particularly during the monumental uprisings of 1905-1917, and presents a significant reinterpretation of a decisive period of Russian--and world--history."--Jacket.